Primary site surgery of de novo stage IV HER2-positive breast cancer in the era of new drug treatments - Guanyu Lu; Lin Jia; Ruohan Yang; Yutong Liu; Zheng Lv; Jiuwei Cui (Frontiers in Oncology, 2024)
ObjectiveThe surgical treatment of the primary site has been a subject of controversy in patients with de novo metastatic breast cancer. In recent years, studies using large databases and retrospective analyses have provided evidence of the survival benefits of localized surgery for these patients. However, due to the improved prognosis associated with novel antitumor agents and the widespread use of anti-HER2 therapy, it is important to investigate the role of primary site surgery in the context of new drug treatments for stage IV HER2-positive breast cancer.MethodsThis retrospective analysis included patients with metastatic breast cancer at diagnosis who were consulted at the First Hospital of Jilin University between 2016 and 2022. We compared the patients’ clinical and pathological characteristics, treatment regimens, and prognosis between the surgery and non-surgery groups.ResultsA total of 96 patients with stage IV HER2-positive breast cancer were included in the study, with 24 patients (25%) undergoing surgery for the primary lesion. Patients with lower Eastern Cooperative Oncology Group (ECOG) scores, earlier T-stage, metastases confined to one organ/site, and fewer metastases were more likely to undergo surgery. Patients in the surgical group had longer progression-free survival (median 25.7 vs. 15.9 months, p=0.073) and overall survival (median 79.1 vs. 48 months, p=0.073) compared to patients in the non-surgical group, however, there was no statistical difference. Univariate and multivariate Cox regression analysis suggested that the choice of first-line targeted therapy regimens rather than surgical treatment influenced the patients’ prognoses. In the subgroup of patients receiving first-line targeted therapy with trastuzumab plus pertuzumab, the decision to undergo surgery on the primary site did not have a statistically significant effect on prognosis.ConclusionPrimary site surgery does not improve the prognosis of de novo stage IV HER2-positive breast cancer. In the era of anti-HER2 therapy, primary surgery is not recommended, except in exceptional circumstances.